A new spatial-domain thermoreflectance method to measure a broad range of anisotropic in-plane thermal conductivity. (1st August 2022) - Jiang, Puqing; Wang, Dihui; Xiang, Zeyu; Yang, Ronggui; Ban, Heng
Highlights: Accurate measurements of a broad range of in-plane thermal conductivity from 1-2000 W/(mK) with a typical uncertainty of <5%. Simultaneously determining the laser spot size with an uncertainty of <2%. Measurements of sub-millimeter scale samples with a lateral size >0.1 mm. Measurements of the anisotropic in-plane thermal conductivity tensor even using an elliptical laser spot. Abstract: In-plane thermal conductivities of small-scale samples are hard to measure, especially for the lowly conductive ones and those lacking in-plane symmetry (i.e., transversely anisotropic materials). State-of-the-art pump-probe techniques including both the time-domain and the frequency-domain thermoreflectance (TDTR and FDTR) are advantageous in measuring the thermal conductivity of small-scale samples, and various advanced TDTR and FDTR techniques have been developed to measure transversely anisotropic materials. However, the measurable in-plane thermal conductivity ( k i n ) is usually limited to be > 10 W / ( m · K ) . In this work, a new spatial-domain thermoreflectance (SDTR) method has been developed to measure a broad range of k i n of millimeter-scale small samples, including those lacking in-plane symmetry, extending the current limit of the measurable k i n to as low as 1 W / ( m · K ) . This SDTR method establishes a new scheme of measurements using the optimized laser spot size and modulation frequency and a new scheme of data processing, enabling measurements of in-plane thermal conductivity tensors of a broad range of k i n values with both high accuracy and ease of operation. Some details such as the requirement on the sample geometry, the effect of the transducer layer, and the effect of heat loss are also discussed. As a verification, the k i n of some transversely isotropic reference samples with a wide range of k i n values including fused silica, sapphire, silicon, and highly ordered pyrolytic graphite (HOPG) have been measured using this new SDTR method. The measured k i n agree perfectly well with the literature values with a typical uncertainty of <5%. As a demonstration of the unique capability of this method, the in-plane thermal conductivity tensor of x-cut quartz, an in-plane anisotropic material, has also been measured.